Identification and Quantification of Bisphenols in Water by Dissipation followed by Silylation using Gas Chromatography-Mass Spectrometry Analysis - Narasimha Raju Katari, B.V.; Madhu, Vemula; Nowduri, Annapurna; Kaliyaperumal, Muralidharan; Swamy Rumalla, Chidananda (Asian Journal of Chemistry, 2022)
Bisphenols are important endocrine disruptors, which were widely used in the variety of food packing and storage materials which often come into contact with various food products packed in them. The presence of bisphenols in water is harmful for the health of humans as well as aquatic animals and also, they accumulate over a period of time. Hence, the present work aimed to develop a simple and accurate GCMS-SIM method for the quantification of bisphenols in packaged drinking water as well as the water samples collected in river and lakes in Andhra Pradesh state of India. Bisphenols were extracted by simple solvent extraction with acetonitrile and silylated by N,O-bis(trimethylsilyl)trifluoro acetamide and analyzed by GC-MS. Various parameters that affect the recovery of the analytes were carefully optimized and the developed method was validated. The recoveries of the analytes were in the range of 80-120 % with quantification limit of 1 ng/L. The calibration curve was linear in the concentration range of 5 ng/L to 10 μg/L. The method was applied for the quantification of bisphenols in packaged drinking water at room temperature and at 50 ºC at various time intervals. The results proved that the water sample kept at room temperature doesn’t shows peaks corresponding to bisphenols. The water sample exposed to 50 ºC for 30 days bisphenols content 10, 12, 22 and 8 ng/L respectively for bisphenol G (BPG), bisphenol F (BPF), bisphenol E, (BPE) and bisphenol A (BPA) whereas the same sample at 180 days of exposer shows 60, 51, 61 and 22 ng/L respectively confirms that the leaching of plastic due to temperature increases the bisphenols level. Among the real time samples studied, the bisphenols level was observed to be very high in Kolleru Lake and it is having 17, 14, 8 and 12 ng/L of BPG, BPF, BPE and BPA, respectively confirms that due to high plastic pollution the bisphenols level was high in these samples. Hence, it can be concluded that the method can be suitable for the analysis of bisphenols in drinking water as well as in wastewater samples.